Persembahan Yang Layak Di Hadapan Tuhan Ditinjau Dari Kejadian 4:1-16 - Wasti Wasti; Yublina kasse (Jurnal Pendidikan Agama dan Teologi, 2023)
Humans are basically spiritual beings. Because, a person can mentally react to something. Humans have always tried to relate to the divine. So the relationship with the god is in the form of worship. The concept of worship in both the Old and New Testaments is the same concept. The Hebrew word for century and the Greek for the beginning of latreia denote the occupation of slaves. And to perform "worship". Before Allah, then His servants must bow down in fear of adoration full of awe, awe and respect. This is the concept behind one's operation in every sacrificial activity in every ministry. Likewise with the implementation of public worship believing in the Lord Jesus. Human sacrifices given as thanksgiving offerings to God are part of worship. No after service offers. This is because the offer is not simply a symbol of giving with what one has, whether in money, or in kind, or in some other way. But the best thing about an offer is that to whom the offer is made the Lord Jesus must be based on faith or the right foundation of a gift from someone else or for some other purpose. Almost all forms of worship are carried out by Sunday schools for children, youth, youth, mothers, fathers, parents, Sunday services and other services bringing offerings of thanks for being part of the service. But the gift must be well understood and taken seriously.